1980
DOI: 10.1038/283664a0
|View full text |Cite
|
Sign up to set email alerts
|

Two distinct factors are required for induction of T-cell growth

Abstract: The molecular and cellular basis of T-lymphocyte activation remains a central question in immunology. The growth of already proliferating T cells is known to depend on T-cell growth factor (TCGF), a physiological mitogen. Noncycling T lymphocytes, however, are not sensitive to TCGF. They require a short contact with mitogenic lectins, such as concanavalin A (Con A) or leukoagglutinin to bind and respond to TCGF, and will thereafter maintain exponential growth for long periods provided that TCGF is not limiting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
96
0
3

Year Published

1981
1981
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 397 publications
(103 citation statements)
references
References 15 publications
4
96
0
3
Order By: Relevance
“…Recently, several other investigators (15)(16)(17)(18)(19) have demonstrated a requirement for the macrophage product, interleukin 1 (IL-1), in the production of IL-2 by murine lymphocytes. Moreover, Maizel et al (20) reported that human monocyte-produced IL-1 augments lectin-stimulated mitogenesis of human T cells purified from peripheral blood.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, several other investigators (15)(16)(17)(18)(19) have demonstrated a requirement for the macrophage product, interleukin 1 (IL-1), in the production of IL-2 by murine lymphocytes. Moreover, Maizel et al (20) reported that human monocyte-produced IL-1 augments lectin-stimulated mitogenesis of human T cells purified from peripheral blood.…”
Section: Resultsmentioning
confidence: 99%
“…IL-1 constitutes a second signal for T cell activation provided by APC carrying the first signal, i.e. MHC class II molecules [6][7][8]. In vitro, IL-1 upregulates the activity of T helper cells, possibly influencing the balance between different subsets [2,9].…”
Section: Introductionmentioning
confidence: 99%
“…Initially, antigen interacts with the T-cell antigen receptor, which leads to the transition from Go to GI and the expression of interleukin 2 (IL-2) receptor and lymphokines including IL-2. Further GI progression requires additional signals provided by the interaction of IL-2 with its high-affinity receptor, which results in the expression of genes related to G, activation, and binding of prolactin to its receptor, which results in entry into S phase and DNA replication (11,14,35,38,67).…”
mentioning
confidence: 99%